The Implementation of Individual Waqf to Foundations for Land Management Rights (HPL) - Astuti, Sera (TABELLIUS: Journal of Law, 2023)
This research aims to know and analyze the implementation of Waqf from private individuals to Educational Foundations on Land Management Rights (HPL). The method used in this research is Sociological juridical, namely a research approach that studies the influence of society on, the extent to which the symptoms that exist in society can influence and vice versa. Sociological juridical research uses secondary data as initial data, which is then followed by primary data or field data, meaning besides seeing Act No. 41 of 2004 concerning Waqf, researchers also saw directly what happened in the field or field research. The types and sources of data that the authors used in this study used primary data that the authors collected directly through interviews as primary data and supported by secondary data. includes laws and regulations books, articles, journals, from the results of the author's research it is possible to carry out personal Waqf to educational foundations on land with management of Land Management Rights (HPL) managed by the Batam Concession Agency (BP) Waqf Land Objects on Land with Management Rights with the type of Building Use Rights (HGB), as well as Usage Rights (HP) can be given a Waqf Rights Period within a certain period of time until the HGB or Rights Use ends or forever with the condition of obtaining written permission / release from the HPL holderKeywords: Implementation; Land; Management; Waqf.